The Relationship Between Organizational Culture And Knowledge Sharing In Organization - Japri, Siti Eirie Afrinah; Lim, Sheilla Omar Lim; Heng, Chin Siong (Universiti Malaysia Sarawak, UNIMAS, 2014)
This study aims to examine the relationship between organizational culture and knowledge sharing in organization. A quantitative approach was used whereby data were collected from 99 respondents through a structured questionnaire that were distributed personally to the respective workplace. The study revealed that organizational culture has influence on knowledge sharing in organization. The results of the study imply that leadership, trust, and communication are important concern for individuals and organizations alike because of its positive consequences on knowledge sharing in organization. Practical implications of these findings and recommendation for organization and future researcher are also discussed.